If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 12 = 3b + -31 Reorder the terms: 12 + 2b = 3b + -31 Reorder the terms: 12 + 2b = -31 + 3b Solving 12 + 2b = -31 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 12 + 2b + -3b = -31 + 3b + -3b Combine like terms: 2b + -3b = -1b 12 + -1b = -31 + 3b + -3b Combine like terms: 3b + -3b = 0 12 + -1b = -31 + 0 12 + -1b = -31 Add '-12' to each side of the equation. 12 + -12 + -1b = -31 + -12 Combine like terms: 12 + -12 = 0 0 + -1b = -31 + -12 -1b = -31 + -12 Combine like terms: -31 + -12 = -43 -1b = -43 Divide each side by '-1'. b = 43 Simplifying b = 43
| 24=6x-2x | | Z+1.5=-2.5 | | 21=-4a+7a | | 5(s+2)=7(s-1) | | 30-3n=2(6-3n) | | 65=2y-5 | | x^2+14x-176=0 | | .9(y+1.4)=-1.8 | | -8t=n+v | | f(x)=2x^2+4x+1.5 | | -8(-7-5n)=-32-4n | | 13j+52=1 | | 8x=14+1x | | -59=5(1-8x)-7(1-3x) | | 21=15-r | | 30*15=x | | 3+9n=22 | | 5(3x+7)=3(7+8x) | | 3(8+6v)+8=-40+6v | | 4(1-7a)=88 | | 10c^2+29c-21=0 | | 11m+13=m+24 | | 9j+5=67 | | 90=5(-2-5n) | | 20y^2+17y+3= | | 7-3x=x+-4(2+x) | | x^2+14x-182=0 | | 9j+5=30 | | 2(-8x+6)=-84 | | -7(2x+8)=-126 | | 9=17u-8u | | 10v^2+43v-9=0 |